Prevalence of Age-Associated Testosterone Deficiency Syndrome in Indian Population - Ghanendra Kumar Yadav; Mrinal Pahwa; Mahendra Singh; Vipin Tyagi; Sudhir Chadha (Advances in Urology)
Testosterone deficiency syndrome (TDS) is a gradual age-related phenomenon that occurs in a large proportion of the aging male population. This current prospective study was done with the objective to estimate the prevalence of age-associated TDS in India and its clinical profile. A total of 800 male patients aged ≥40 year were approached to participate in the study. A brief history and focused examination was done. Based on our exclusion criteria, 55 patients were excluded. Androgen deficiency in aging male (ADAM) questionnaire was administered to all remaining 745 patients. Out of these 745 patients, ADAM-positive (symptomatic TDS) patients were found to be 359 and enrolled in the study. In all ADAM-positive patients, serum testosterone levels were measured. Prevalence of symptomatic TDS in study population was found to be 48.18%. Mean total and free testosterone level of symptomatic TDS population were 3.287 ± 1.494 ng/ml (1.12–9.61) and 7.476 ± 2.902 pg/ml (2.18–21.76), respectively. Prevalence of biochemically confirmed TDS among symptomatic TDS population was 60.17%. Prevalence of TDS increases progressively with each decade of life (p=0.034). Prevalence was higher in patients with diabetes, hypertension, coronary artery disease, obesity, and metabolic syndrome. TDS is a real phenomenon with a prevalence of 28.99% in our study population.